Implementation of Microcirculation Examination in Clinical Practice—Insights from the Nationwide POL-MKW Registry - Rafał Januszek; Łukasz Kołtowski; Mariusz Tomaniak; Wojciech Wańha; Wojciech Wojakowski; Marek Grygier; Wojciech Siłka; Grzegorz Jan Horszczaruk; Bartosz Czarniak; Radosław Kręcki; Bartłomiej Guzik; Jacek Legutko; et al. (Medicina, 2024)
Background and Objectives: The assessment of coronary microcirculation may facilitate risk stratification and treatment adjustment. The aim of this study was to evaluate patients’ clinical presentation and treatment following coronary microcirculation assessment, as well as factors associated with an abnormal coronary flow reserve (CFR) and index of microcirculatory resistance (IMR) values. Materials and Results: This retrospective analysis included 223 patients gathered from the national registry of invasive coronary microvascular testing collected between 2018 and 2023. Results: The frequency of coronary microcirculatory assessments in Poland has steadily increased since 2018. Patients with impaired IMR (≥25) were less burdened with comorbidities. Patients with normal IMR underwent revascularisation attempts more frequently (11.9% vs. 29.8%, p = 0.003). After microcirculation testing, calcium channel blockers (CCBs) and angiotensin-converting enzyme inhibitors were added more often for patients with IMR and CFR abnormalities, respectively, as compared to control groups. Moreover, patients with coronary microvascular dysfunction (CMD, defined as CFR and/or IMR abnormality), regardless of treatment choice following microcirculation assessment, were provided with trimetazidine (23.2%) and dihydropyridine CCBs (26.4%) more frequently than those without CMD who were treated conservatively (6.8%) and by revascularisation (4.2% with p = 0.002 and 0% with p < 0.001, respectively). Multivariable analysis revealed no association between angina symptoms and IMR or CFR impairment. Conclusions: The frequency of coronary microcirculatory assessments in Poland has steadily increased. Angina symptoms were not associated with either IMR or CFR impairment. After microcirculation assessment, patients with impaired microcirculation, expressed as either low CFR, high IMR or both, received additional pharmacotherapy treatment more often.